Caracterización de los pacientes con Labio fisurado y Paladar Hendido atendidos en la Fundación Operación Sonrisa-2020 - Cetina Cepeda, Diana Marcela; Navarro Bonilla, Henry; Torres Gómez, Mayra Alejandra (Universidad Antonio Nariño, 2024)
Cleft lip and palate (CLP) is the most common congenital malformation worldwide. Currently, research reports that it occurs in 1 out of every 700 live births worldwide. In Latin America the prevalence is also high, approximately 1.45 cases in every 1000 children born. In Colombia, according to the ENSAB IV, cleft lip and palate has a prevalence of 0.07%, having a similar behavior in both urban and rural areas.